Research on the Intake Port of a Uniflow Scavenging GDI Opposed-Piston Two-Stroke Engine - Tianyou Pei; Feixue Chen; Shuheng Qiu; Dawei Wu; Weiwei Gao; Zhaoping Xu; Chi Zhang (Energies, 2022)
The intake port structure optimization is very important for the uniflow scavenging opposed-piston two-stroke engine, as the intake port structure affects the scavenging efficiency and turbulence kinetic energy and thus further impacts the engine indicated efficiency. This paper aims at improving the indicated efficiency, presenting a comprehensive study on the intake port optimization concerning both scavenging efficiency and turbulence kinetic energy. First, a three-dimensional model based on computational fluids dynamics is established and validated. Subsequently, different numbers of intake ports are compared and analyzed from the perspectives of the scavenging efficiency and turbulence kinetic energy. Furthermore, the double-ports intake structure is selected with the consideration of the compact structure and high scavenging efficiency. Then, the radial angle and width of the double-ports structure are optimized based on the response surface method. The results show that the optimized structure increases the turbulence kinetic energy in relative high scavenging efficiency. The indicated efficiency exhibits a significant increase within the speed range of 1000–4000 rpm and reaches the maximum value of 39.5% around 2000 rpm.